Out of Sight and Out of Reach: Public Access Strategies Using a Mixed Method to Reconnect a Saudi Urban Mega-District with its Shoreline. Issue 4 (4th July 2022) - Alhajaj, Nawaf; Hendrigan, Cole
Abstract: This study questions global best-practice policies regarding public access to the shorelines of rapidly-growing cities, based on a mega-urban district in Jeddah, Saudi Arabia, where residents are not yet provided with public open space, nor with physical or visual access to the qualitatively desirable shoreline. We applied a policy-led review of local legal frameworks and global best-practices of shoreline public access management, followed by several descriptive research strategies to develop four public access strategies that connect the district with its shoreline. The developed strategies can inform other cities with competing population growth pressures, in providing the health benefits of equitable public shoreline access. The strategies raise new management issues such as shoreline public access locations, capital and operational financing, and ecological consequences.